Assessing E-business and Organizational Performance in Nigeria Today: Evidence from Jumia Ltd, Lagos - Nduji Romanus; Marcus Garvey Orji; Oyenuga Michael Oyedele; Oriaku Chris (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
In the Nigerian Business environment, e-business is becoming an important initiative for companies to consider in every aspect of running a business. Business organizations have given their places to digital economies in a way that electronic technology interprets the language of every business transaction. E-business has gained prominence which has impacted much on the economy. This study aims at assessing e-business and organizational performance in Nigeria Today: Evidence from Jumia Ltd, Lagos. Three objectives were adopted for this study which are, to establish the effect of e-trading on performance of Jumia Ltd, Lagos, to examine the effect of e-marketing on performance of Jumia Ltd, Lagos. And to explore the effect of mobile commerce on performance of Jumia Ltd, Lagos. The research design adopted for this study was the descriptive research design. The target population of the study was 158 employees of the firm under study. This also served as the sample size. Data were obtained through questionnaire. Hypotheses were analyzed using multiple regression technique. The study revealed that e-business has positive effect on performance of Juima Ltd, Lagos. It was concluded that e-business if properly accorded a maximum attention by Jumia Ltd, Lagos would improve the organization marketing and objectives. It was recommended that Customers’ satisfaction should be the watchword for Jumia because customers are the king in any business organization. There should be free flow of information about Jumia and their products.